1453. Ninety-One Day Quality of Life Post-Pneumonia Diagnosis in Adult Patients in Japan. (26th November 2018) - Glick, Henry; Miyazaki, Taiga; Hirano, Katsuji; Suaya, Jose; Gonzalez, Elisa; Gessner, Bradford D; Isturiz, Raul E; Arguedas, Adriano G; Kohno, Shigeru
Abstract: Background: Pneumonia is a serious illness with potentially long-lasting but poorly-characterized impact on quality of life. The Japanese Goto Epidemiology Study is a prospective, active, population-based surveillance study of adults with community-onset pneumonia (COP), that includes assessment of Quality Adjusted Life Years (QALYs). Methods: Patients with X-ray/CT scan confirmed COP enrolled in the Goto study and consented to participate in QALY assessment responded to Japanese versions of EuroQol-5D-5L (EQ-5D-5L) health state classification (primary), EQ-5D visual analog scale, and SF-6D (secondary) instruments. This interim analysis reports 91-day QALYs based on Day 1 (diagnosis), 8, 16, 31, and 91 EQ-5D-5L responses of patients enrolled between June 1, 2017 and February 7, 2008. For comparison, we developed hypothetical QALYs had the patients not developed pneumonia (control) using the EQ-5D-5L scores from Day -30 (via recall) carried forward and adjusted by the natural decline in scores and death with age. QALYs were calculated as the area (trapezoidal method) under the survival weighted pneumonia and control EQ-5D-5L QALY score curves. Results: The 234 patients were 55% male, 88% aged ≥64 years, 45% nursing home residents, and 65% initially hospitalized (35% initially outpatient) for COP. Compliance for interviews among survivors was 100%. EQ-5D-5L scores were 0.732 at Day −30, decreased to 0.590 at diagnosis, and rose to 0.675 by Day 91. The average scores at all time points remained below Day −30 (all P values < 0.01). Compared with hypothetical controls, development of pneumonia on average resulted in a loss of 0.0292 QALYs ( P < 0.001) during the first 91 days of follow-up. Conclusion: Among residents of Goto Island, Japan, significant QALY losses were observed in association with a diagnosis of pneumonia and had not returned to baseline by 3 months after diagnosis. Scores and cumulative QALY losses during the first 3 months after pneumonia diagnosis were comparable to those experienced by US adults with chronic heart failure during a 3-month period. Disclosures: H. Glick, K. Hirano, Pfizer Inc.: Consultant, Research support. T. Miyazaki, Pfizer Inc.: Collaborator, Research support and Speaker honorarium. . J. Suaya, E. Gonzalez, B. D. Gessner, A. G. Arguedas, Pfizer Inc.: Employee and Shareholder, Salary. R. E. Isturiz, Pfizer, Inc: Employee and Shareholder, Salary and Stock & Stock Options. . S. Kohno, Pfizer Inc.: Consultant, Research support and Speaker honorarium.